Marketing de relacionamento: a fidelização de clientes e o endomarketing na indústria de produtos orgânicos - Graziano, Graziela Oste (2011)
The purpose of this study was to analyze the results and present the statistical programs of employment relationship marketing in its tracks: Loyalty Programs and Programs Endomarketing in a specific branch of the agribusiness sector, the organic products. In preparing the study was the exploratory research used to develop and clarify the theoretical concepts related to the topic, observational research to raise the companies producing organic market and questionnaires with open and closed questions to identify the profile of the programs Loyalty programs and Endomarketing they use. Were investigated in the survey 12 companies, 24 companies in the survey by observation in supermarket chains, and thus a convenience sample. It can be concluded with the analysis of the results that the Relationship Marketing, in its Customer Loyalty Programs and Endomarketing is employed by industries processing organic products. The types of loyalty programs offered by the more organic products industries were the Consumer Service Center (SAC), disclosure of revenue, merchandising and tips from health professionals. The types of programs are offered Endomarketing: organizational culture, behavior, and organizational climate change, bulletin boards, books, newspapers and pamphlets, quality of life, training and product merchandising. Thus, one can say that there is a higher incidence of the use of loyalty programs compared to programs endomaketing industries surveyed.